Experimental results of a High-Temperature-ATES field test: Induced convection, heat conduction and groundwater flow as efficiency-reducing processes - Johannes Nordbeck; Götz Hornbruch; Klas Lüders; Jan Niklas Nordheim; Ulrike Werban; Carsten Vogt; Hans Richnow; Sebastian Bauer (Geothermics, 2026)

Integrating hydraulic and thermal constraints for ATES well placements: An analytical approach - Jan Niklas Nordheim; Christof Beyer; Sebastian Bauer (Hydrogeology Journal, 2026)
Aquifer thermal energy storage (ATES) mitigates the seasonal mismatch between summertime heat supply and wintertime heat demand, contributing to decarbonization of the heating and cooling sector. Conventional low-temperature ATES design targets high-transmissivity aquifers to achieve the pumping rates needed to meet energy demand. If geological constraints or competing subsurface uses require storage in lower-transmissivity formations, pumping rates may be restricted to limit hydraulic head changes or reduce the risk of well screen particle clogging. This restriction would increase the number of well doublets and potentially make well field layout a critical design challenge. To address this complexity at an early planning stage, an analytical approach is presented that determines the minimum number and distance of ATES well doublets assuming a checkerboard or a lane layout. The approach combines thermal and hydraulic constraints by determining a minimum well distance derived from the thermal radius and a maximum well distance necessary to limit pumping-induced head changes, explicitly accounting for hydraulic superposition effects in multi-doublet well fields. Applying this approach to a planned low-temperature ATES at Kiel University, Germany, shows that the checkerboard layout achieves the target pumping rate of 200 m 3 /h with nine well doublets, whereas the lane layout requires 11 well doublets. The analysis also indicates that reducing the distance between wells of the same type in low-transmissivity aquifers significantly increases the number of well doublets. The approach provides a practical tool for preliminary ATES design, supporting informed well field configuration under hydraulic constraints.

Impact of subsurface heterogeneity and thermally induced buoyancy-driven flow on high-temperature aquifer thermal energy storage - Stefan Heldt; Christof Beyer; Sebastian Bauer (Geothermics, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Rapid growth of thermophilic bacteria during a high-temperature aquifer thermal energy storage (HT-ATES) field experiment - Nina S. Keller; Klas Lüders; Götz Hornbruch; Johannes Nordbeck; Sebastian Bauer; Andreas Dahmke; Hans H. Richnow; Carsten Vogt (Water Research, 2026)

A workflow for estimating injection pressure limits for CO2 storage: A reservoir-geomechanical analysis of a candidate site in the German North Sea sector - Firdovsi Gasanzade; Hendrawan Diandaru Bayu Aji; Frank Wuttke; Sebastian Bauer (International Journal of Greenhouse Gas Control, 2026)

Benchmarking CO₂ storage simulations: Results from the 11th Society of Petroleum Engineers Comparative Solution Project - Jan M. Nordbotten; Martin A. Fernø; Bernd Flemisch; Anthony R. Kovscek; Knut-Andreas Lie; Jakub W. Both; Olav Møyner; Tor Harald Sandve; Etienne Ahusborde; Sebastian Bauer; Zhangxing Chen; Holger Class; et al. (International Journal of Greenhouse Gas Control, 2025)

Current research on aquifer thermal energy storage (ATES) in Germany - Ruben Stemmle; Alireza Arab; Sebastian Bauer; Christof Beyer; Guido Blöcher; Claire Bossennec; Maximilian Dörnbrack; Florian Hahn; Philip Jaeger; Stefan Kranz; Alexandra Mauerberger; Jan Niklas Nordheim; et al. (Grundwasser, 2025)
This paper reviews the current research on aquifer thermal energy storage (ATES) and mine thermal energy storage (MTES) in Germany providing descriptions of 3 low-temperature ATES (LT-ATES), 8 high-temperature ATES (HT-ATES), and 2 MTES research sites. While the overview reveals a diverse field of investigations spanning various spatial scales, research objectives, and methodologies, the predominant focus is limited to early-stage research with low technology readiness levels (TRL). The high number of HT-ATES research sites suggests greater research interest compared to LT-ATES. The integration of ATES into district heating (DH) grids in particular is a prominent research focus, yet almost none of the projects are specifically intended for practical implementation. Future research should therefore prioritize real-world demonstration projects and identify key locations, which is crucial for showcasing the benefits of ATES. The need for a streamlined regulatory framework that addresses environmental risks and ensures installation quality and efficient permit procedures is also discussed.

Thermo- and light responsive microgels for efficient brackish and seawater forward osmosis desalination - Amir Jangizehi; Jan Eckhardt; Karolina Izabela Borkowska; Zsolt Dallos; Melanie Bauer; Hasan Salehi; Reza Razavi; Alireza Shakeri; Seyed Abdollatif Hashemifard; Sebastian Seiffert (Desalination, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Uncertainty assessment of thermal recovery and subsurface temperature changes induced by high-temperature aquifer thermal energy storage (HT-ATES): A case study - Stefan Heldt; Christof Beyer; Sebastian Bauer (Geothermics, 2024)

Conceptualizing sustainable participation in the context of German football supporters - Sebastian Björn Bauers; Sandy Adam; Michael Fuchs; Leon Piotrowski; Gregor Hovemann (German Journal of Exercise and Sport Research, 2024)
Institutionalized supporter participation is a traditional part of German professional football clubs. Due to commercialization, some challenging issues have arisen in recent years regarding supporter participation. To develop new approaches for improving participation, the study uses a social sustainability perspective, illustrating that social sustainability elements help to develop and structure the potential for improvement of participation in German professional football. By identifying and discussing links between social sustainability and institutionalized supporter participation, we contribute to the conceptualization of sustainable participation. Our research supports the creation of an inclusive and sustainable fan community where fans can actively participate in decisions and actions that affect their current and future fandom environment. Based on the social sustainability principles of health, influence, competence, impartiality, and meaning-making, we compile the following characteristics of sustainable participation: social well-being oriented participation, direct influence, regular voting rights, representative participation, appealable resolutions, information-based participation, barrier-free participation, democratic voting, established constitutions, and encouraged participation. This conceptualization provides approaches and foundations for future investigations regarding participation research in football and practical implications for member associations, association members, league organizers, and other stakeholders to establish and improve institutionalized participation.

Cross-well multilevel pumping tests – A novel approach for characterizing the changes of hydraulic properties during gas storage in shallow aquifers - Linwei Hu; Maike Schnackenberg; Götz Hornbruch; Klas Lüders; Wolf Tilmann Pfeiffer; Ulrike Werban; Sebastian Bauer (Journal of Hydrology, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Processing of carbon-reinforced construction materials releases PM2.5 inducing inflammation and (secondary) genotoxicity in human lung epithelial cells and fibroblasts - Jana Pantzke; Arne Koch; Elias J. Zimmermann; Narges Rastak; Svenja Offer; Christoph Bisig; Stefanie Bauer; Sebastian Oeder; Jürgen Orasche; Petra Fiala; Michael Stintz; Christopher P. Rüger; et al. (Environmental Toxicology and Pharmacology, 2023)

The OGS-Eclipse code for simulation of coupled multiphase flow and geomechanical processes in the subsurface - Katharina Benisch; Wenqing Wang; Jens-Olaf Delfs; Sebastian Bauer (Computational Geosciences, 2020)
This paper presents a numerical simulation tool for the analysis of coupled processes related to subsurface operations. The tool combines the open-source scientific code OpenGeoSys with the reservoir simulator Eclipse enabling the coupling of thermal, hydraulic, mechanical and geochemical processes. While the coupling of multiphase flow with heat and reactive geochemical component transport has been already implemented, OpenGeoSys-Eclipse is now extended for the coupling of multiphase flow and deformation. By this, OpenGeoSys-Eclipse is capable of addressing the impact of pore pressure changes on rock stability and deformation as well as the feedback effects of geomechanical processes on multiphase flow via pore volume coupling and porosity and permeability update. The coupling is verified by several test cases of gas storage scenarios and compared with reference simulations of OpenGeoSys. The results are in good agreement regarding the general effects of geomechanical feedback on pore pressure as well as porosity and permeability changes. Differences in the results are only observed for the pore volume coupling arising from the different implementation of rock compressibility models in the two simulators. The simulations are furthermore used to investigate the relevance of addressing geomechanical feedback in numerical scenario simulations for the assessment of subsurface operations. The results show clearly, that, depending on the given storage site conditions and rock types, the feedback of deformation on pore pressure can be significant and should therefore be accounted for in the assessment.

The regulation of investors’ influence in German professional football - Sebastian Björn Bauers; Gregor Hovemann (German Journal of Exercise and Sport Research, 2019)

Carbon isotope composition, water use efficiency, and drought sensitivity are controlled by a common genomic segment in maize - Viktoriya Avramova; Adel Meziane; Eva Bauer; Sonja Blankenagel; Stella Eggels; Sebastian Gresset; Erwin Grill; Claudiu Niculaes; Milena Ouzunova; Brigitte Poppenberger; Thomas Presterl; Wilfried Rozhon; et al. (Theoretical and Applied Genetics, 2019)

Cellular distribution of CD200 receptor in rats and its interaction with cytomegalovirus e127 protein - Mohamed A. El-Mokhtar; Agnieszka Bauer; Julia Madela; Sebastian Voigt (Medical Microbiology and Immunology, 2018)

LCA of mobility solutions: approaches and findings—66th LCA forum, Swiss Federal Institute of Technology, Zurich, 30 August, 2017 - Rolf Frischknecht; Christian Bauer; Andreas Froemelt; Stefanie Hellweg; Kirsten Biemann; Thomas Buetler; Brian Cox; Peter de Haan; Sebastian Hoerl; René Itten; Niels Jungbluth; Yorick Ligen; et al. (The International Journal of Life Cycle Assessment, 2018)

Report on the 43rd Annual Meeting of the DPG-Working Group Nematology - Matthias Daub; Ulrike Hakl; Leendert PG Molendijk; Corrie Schomaker; Thomas H Been; Thea G van Beers; Sevda Jivishova; Emil Jivishov; Michael Keusgen; Roman Bluemel; Daniel Fischer; Florian MW Grundler; et al. (Journal of Plant Diseases and Protection, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Nanoscale engineering of biomimetic surfaces: cues from the extracellular matrix - Klaus von der Mark; Jung Park; Sebastian Bauer; Patrik Schmuki (Cell and Tissue Research, 2010)

A study of preferential flow in heterogeneous media using random walk particle tracking - Chan-Hee Park; Christof Beyer; Sebastian Bauer; Olaf Kolditz (Geosciences Journal, 2008)

Cadmium, cobalt and lead cause stress response, cell cycle deregulation and increased steroid as well as xenobiotic metabolism in primary normal human bronchial epithelial cells which is coordinated by at least nine transcription factors - Felix Glahn; Wolfgang Schmidt-Heck; Sebastian Zellmer; Reinhard Guthke; Jan Wiese; Klaus Golka; Roland Hergenröder; Gisela H. Degen; Thomas Lehmann; Matthias Hermes; Wiebke Schormann; Marc Brulport; et al. (Archives of Toxicology, 2008)

The extent of induction of CYP3A by St. John’s wort varies among products and is linked to hyperforin dose - Silke C. Mueller; Jolanta Majcher-Peszynska; Bernhard Uehleke; Sebastian Klammt; Ralf G. Mundkowski; Wolfram Miekisch; Hartwig Sievers; Steffen Bauer; Bruno Frank; Guenther Kundt; Bernd Drewelow (European Journal of Clinical Pharmacology, 2006)

Tiefenorientierte integrale Erkundung der Schadstoffbelastung in grorumig kontaminierten Aquiferen - Thomas Ptak; Marti Bayer-Raich; Sebastian Bauer (Grundwasser, 2004)

Gap junction remodeling and altered connexin43 expression in the failing human heart - Sawa Kostin; Markus Rieger; Sebastian Dammer; Stefan Hein; Manfred Richter; Wölf-Peter Klövekorn; Erwin P. Bauer; Jutta Schaper (Molecular and Cellular Biochemistry, 2003)

Erratum to: Impaired sodium excretion, decreased glomerular filtration rate and elevated blood pressure in endothelin receptor type B deficient rats - Berthold Hocher; Christoph Dembowski; Torsten Slowinski; Sebastian T. Friese; Anja Schwarz; Anna-Leena Siren; Hans-H. Neumayer; Christa Thöne-Reineke; Christian Bauer; Benno Nafz; Hannelore Ehrenreich (Journal of Molecular Medicine, 2001)

Impaired sodium excretion, decreased glomerular filtration rate and elevated blood pressure in endothelin receptor type B deficient rats - Berthold Hocher; Christoph Dembowski; Torsten Slowinski; Sebastian T. Friese; Anja Schwarz; Anna-Leena Siren; Hans-H. Neumayer; Christa Thöne-Reineke; Christian Bauer; Benno Nafz; Hannelore Ehrenreich (Journal of Molecular Medicine, 2001)